2021
DOI: 10.20473/jafh.v11i1.26741
|View full text |Cite
|
Sign up to set email alerts
|

The Growth of Tilapia (Oreochromis niloticus) with the Addition of Probiotics to Feed in Sakatiga Village, Indralaya District, Ogan Ilir Regency, South Sumatera

Abstract: Feed is a source of energy to support the growth and survival of fish. To increase feed consumption to the maximum, it is necessary to add an intake to fish feed to increase the digestibility of fish to feed. One alternative that can be done is by adding (supplements) to the feed. Probiotics are an alternative that can be used as a supplement to aquaculture fish feed. The purpose of this field practice is to determine the effect of adding probiotics on the growth of tilapia. This field practice was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…The high SGR value explains that the treatment has a big influence on the growth rate. Research related to the use of probiotics on the growth rate of tilapia showed that the addition of probiotics increased the growth rate of tilapia in accordance with this study [9].…”
Section: Discussionsupporting
confidence: 89%
“…The high SGR value explains that the treatment has a big influence on the growth rate. Research related to the use of probiotics on the growth rate of tilapia showed that the addition of probiotics increased the growth rate of tilapia in accordance with this study [9].…”
Section: Discussionsupporting
confidence: 89%
“…Laju pertumbuhan spesifik adalah persentase peningkatan ukuran ikan yang dihasilkan dari selang bobot akhir dan awal ikan yang dibagi akumulasi waktu pemeliharaan (Sinaga et al, 2022). Data SGR yang dihasil dalam penelitian ini disajikan pada Gambar 1.…”
Section: Hasil Laju Pertumbuhanunclassified
“…With the maintenance interval as a dividing element of absolute growth results, the daily rate of growth of snapper fish is produced (Sinaga & Mukti, 2022) whose data are summarized in Table 1. giving mangosteen rind flour 4 gr/kg feed 2.28%, then treatment B with a dose giving mangosteen rind flour 2 gr/kg feed obtained an average value of 2.26% and a daily growth rate of seed weight The lowest white sea bass was obtained in treatment A without giving mangosteen peel flour, obtaining an average value of 2.19%.…”
Section: Daily Growth Ratementioning
confidence: 99%